Current gaps in sepsis immunology: new opportunities for translational research - Rubio, Ignacio; Uhle, Florian; Weigand, Markus A. (The lancet. Infectious diseases, 2019)
Increasing evidence supports a central role of the immune system in sepsis, but the current view of how sepsis affects immunity, and vice versa, is still rudimentary. The European Group on Immunology of Sepsis has identified major gaps that should be addressed with high priority, such as understanding how immunological alterations predispose to sepsis, key aspects of the immunopathological events during sepsis, and the long-term consequences of sepsis on patient's immunity. We discuss major unmet topics in those three categories, including the role of key immune cells, the cause of lymphopenia, organ-specific immunology, the dynamics of sepsis-associated immunological alterations, the role of the microbiome, the standardisation of immunological tests, the development of better animal models, and the opportunities offered by immunotherapy. Addressing these gaps should help us to better understand sepsis physiopathology, offering translational opportunities to improve its prevention, diagnosis, and care.